Economic value and socio-cultural determinants of non-timber forest products harvesting in the W Transboundary Biosphere Reserve, Benin (Revista Espinhaço, 2019)
This paper examined the economic value of non-timber forest products and their contribution to cash income of people living around the W Transbundary Bioreserve of W in Benin. 148 people among two ethnic groups were interviewed. Data were analysed using the indirect method of opportunity cost and raw margin estimation. Results showed that local people use to harvest mostly five products: one non-marketable product (firewood) and four marketable products (almonds of Vitellaria paradoxa, C.F.Gaertn, seeds and pulp of Parkia biglobosa (Jacq.) R. Br. ex G. Don and leaves of Adansonia digitata L.). The mean contribution of marketable products to surveyed dwellers was estimated at XOF 255,484 ($US 510.968) (standard error: XOF 37,109), representing about 11.46% of the annual cash income per household. Age and sociolinguistic group were the main determinants of non-timber forest products harvesting. Given their value to the communities, those plants should be prioritized for domestication and conservation.
Keywords: non-timber forest products; economic value; West Africa